TORQUE OF A SLOTLESS AXIAL-FLUX PERMANENT MAGNET TORQUE MOTOR WITH SOLID SLITTED STATOR YOKE - І.С. Пєтухов; В.Г. Кіреєв; К.П. Акинін; Є.В. Ісаєв (Технічна електродинаміка)
A three-phase slotless torque motor of axial structure with permanent magnets and a solid stator core is considered. The effect of circular slits in the core, preventing the flow of eddy currents, is investigated. It is noted that the magnetic field of the stator winding has a minimum effect on the field created by permanent magnets and it can be neglected. Two stages of the study are defined: the first is the determination of the maximum torque in a static state, and the second is the determination of losses from motional eddy currents during the movement of the stator core relative to the rotor. The field problem was solved using the software "COMSOL Multiphysics". A smooth analytical function was used to approximate the magnetisation curve of core steel. It has been demonstrated through simulation of the physical model that implementing four slits can reduce torque loss approximately by four times or increase the maximum rotational speed of the rotor by the same amount. References 8, figures 9, table 1.